Diffuse alveolar hemorrhage after hematopoietic cell transplantation- response to treatments and risk factors for mortality - Schoettler, Michelle L.; Dandoy, Christopher E.; Harris, Anora; Chan, Marilynn; Tarquinio, Keiko M.; Jodele, Sonata; Qayed, Muna; Watkins, Benjamin; Kamat, Pradip; Petrillo, Toni; Obordo, Jeremy; Higham, Christine S.; et al. (Frontiers in Oncology, 2023)
Diffuse alveolar hemorrhage (DAH) is a life-threatening complication of hematopoietic cellular therapy (HCT). This study aimed to evaluate the effect of DAH treatments on outcomes using data from consecutive HCT patients clinically diagnosed with DAH from 3 institutions between January 2018-August 2022. Endpoints included sustained complete response (sCR) defined as bleeding cessation without recurrent bleeding, and non-relapse mortality (NRM). Forty children developed DAH at a median of 56.5 days post-HCT (range 1-760). Thirty-five (88%) had at least one concurrent endothelial disorder, including transplant-associated thrombotic microangiopathy (n=30), sinusoidal obstructive syndrome (n=19), or acute graft versus host disease (n=10). Fifty percent had a concurrent pulmonary infection at the time of DAH. Common treatments included steroids (n=17, 25% sCR), inhaled tranexamic acid (INH TXA,n=26, 48% sCR), and inhaled recombinant activated factor VII (INH fVIIa, n=10, 73% sCR). NRM was 56% 100 days after first pulmonary bleed and 70% at 1 year. Steroid treatment was associated with increased risk of NRM (HR 2.25 95% CI 1.07-4.71, p=0.03), while treatment with INH TXA (HR 0.43, 95% CI 0.19- 0.96, p=0.04) and INH fVIIa (HR 0.22, 95% CI 0.07-0.62, p=0.005) were associated with decreased risk of NRM. Prospective studies are warranted to validate these findings.